Greenlandic attitudes towards Norwegians and Danes from Nansen’s icecap crossing to the 1933 World Court verdict in The Hague - Langgård, Karen (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2014)
After Fridtjof Nansen (1861-1930) crossed the Greenland icecap, he spent the winter in Nuuk and impressed the Greenlanders not only by demonstrating his skill and daring in kayaking, but also by his openness to Greenlandic food, culture, and traditions. Later on, when Danes and Norwegians came into conflict over Greenland, Greenlanders supported the Danish colonial power against Norway, while at the same criticizing the Danes for not paying enough respect to Greenlanders during the process. Articles from the national Greenlandic newspapers Atuagagdliutit and Avangnâmioĸ demonstrate that Greenlanders were open-minded towards Norwegians but critical towards Danes. They fully supported the latter as a colonial power against Norway, while never refraining from the idea that Greenland remained their ethnic-national territory, even though for the time being it was colonized by the Danes. The author concludes that Greenlandic agency found in these newspapers is very relevant when negotiating today’s discourse on colonial Greenlanders.